2023
DOI: 10.3390/ijms24044080
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Metabolism and Its Role in Temporomandibular Joint Osteoarthritis and Autoimmune Thyroid Diseases

Abstract: The aim of this review was to present the metabolism of vitamin D3, as well as to discuss the role of vitamin D3 in bone metabolism, temporomandibular joint osteoarthritis (TMJ OA), and autoimmune thyroid diseases (AITD) on the basis of the literature. Vitamin D3 plays a significant role in human health, as it affects the calcium-phosphate balance and regulates the bone metabolism. Calcitriol impresses the pleiotropic effect on human biology and metabolism. Its modulative function upon the immune system is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…Vitamin D3 is one of the most important fat-soluble essential nutrients and is normally produced from 7-dehydrocholesterol when exposed to ultraviolet light. It has been reported that vitamin D3 has a significant impact on human health by affecting the calcium-phosphate balance and regulating bone metabolism. , Cholesterol, an essential component of cell membranes, acts as a specific precursor for steroid hormones and also plays a vital role in maintaining cellular homeostasis and the transduction of intracellular signals . Therefore, vitamin D3 and cholesterol have been demonstrated to be crucial biomolecules in the steroid metabolism network.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D3 is one of the most important fat-soluble essential nutrients and is normally produced from 7-dehydrocholesterol when exposed to ultraviolet light. It has been reported that vitamin D3 has a significant impact on human health by affecting the calcium-phosphate balance and regulating bone metabolism. , Cholesterol, an essential component of cell membranes, acts as a specific precursor for steroid hormones and also plays a vital role in maintaining cellular homeostasis and the transduction of intracellular signals . Therefore, vitamin D3 and cholesterol have been demonstrated to be crucial biomolecules in the steroid metabolism network.…”
Section: Resultsmentioning
confidence: 99%
“…However, Szulc et al . found that vitamin D has an immune-modulator effect and it influences AITDs, including HT, and GD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has pointed out some new types of cell death, such as pyroptosis, parthanatos, ferroptosis, and necroptosis (22)(23)(24). A caspase-1/4/5/11 involved proinflammatory programmed cell death terms pyroptosis, which has been elucidated to participate in osteoarthritis (14). Cartilage breakdown is the typical pathological change in osteoarthritis, especially traumatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis has been verified to be associated with the development of arthritis (14), and the inhibition of pyroptosis is also useful in alleviating the process of arthritis (15,16). However, whether the suppression of GSDMD protects the CHs from pyroptosis in traumatic arthritis remains unclear.…”
Section: Introductionmentioning
confidence: 99%